2013
DOI: 10.1073/pnas.1303906110
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of B-cell exosome proteins by gamma herpesvirus infection

Abstract: The human gamma herpesviruses, Kaposi sarcoma-associated virus (KSHV) and EBV, are associated with multiple cancers. Recent evidence suggests that EBV and possibly other viruses can manipulate the tumor microenvironment through the secretion of specific viral and cellular components into exosomes, small endocytically derived vesicles that are released from cells. Exosomes produced by EBV-infected nasopharyngeal carcinoma cells contain high levels of the viral oncogene latent membrane protein 1 and viral microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
223
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(231 citation statements)
references
References 58 publications
4
223
0
1
Order By: Relevance
“…Another oncogene, the melanoma cells secreted Wnt5A was also reported to induce the release of EVs 20 . Finally, tumorigenic viruses such as EBV can manipulate the secretion of EV bound cellular components, namely integrins, actin, IFN, and NFκB that subsequently activate cellular signaling in the surrounding stroma 49 .…”
Section: Modulation Of Ev Compositionmentioning
confidence: 99%
“…Another oncogene, the melanoma cells secreted Wnt5A was also reported to induce the release of EVs 20 . Finally, tumorigenic viruses such as EBV can manipulate the secretion of EV bound cellular components, namely integrins, actin, IFN, and NFκB that subsequently activate cellular signaling in the surrounding stroma 49 .…”
Section: Modulation Of Ev Compositionmentioning
confidence: 99%
“…Even though EBV and KSHV were originally observed in human tumor specimens in 1964 and 1994, respectively, the finding that a portion of the human population was infected by both EBV and KSHV received great attention (Pegtel, 2013). When the two herpesviruses combine in aggressive lymphoma, primary effusion lymphoma (PEL), they can bring about an extraordinary synergic effect on lymphomagenesis, leading to increased complications (Meckes et al, 2013;Choi et al, 2017). A large number of investigations have revealed that these two viruses share similar colonization and persistence strategies, such as deregulating NF-κB to control B-cell proliferation and secreting proinflammatory mediators that contribute to tumorigenesis.…”
Section: Exosomes In Gamma Herpesvirus Infectionmentioning
confidence: 99%
“…The results indicated that exosomes from cells infected by these two viruses probably regulate cell death and survival, protein synthesis, ribosome function, and some signaling pathways. EBVrelated exosomes mainly influence cellular signalings such as NF-κB, IFN, integrins, and actin, whereas KSHVrelated exosomes prevailingly impact cell metabolism (Meckes et al, 2013). Gamma herpesviruses alter metabolic phenotypes to allow viral infection and everlasting persistence, and Angela Kwok-Fung Lo et al speculated that this modulation is conductive to tumor progression, suggesting a new opportunity for therapeutic intervention (Lo et al, 2017).…”
Section: Exosomes In Gamma Herpesvirus Infectionmentioning
confidence: 99%
“…Apart from protumorigenic soluble factors, many tumor cells release endosome-derived vesicles, called exosomes, which mediate intercellular communication. In PNAS, Meckes et al describe that EBV-and KSHV-infected lymphoma cells secrete exosomes with distinct repertoires of cellular proteins (1). In light of recent studies demonstrating that tumor cellderived exosomes exert protumorigenic signaling properties (2), the data presented by Meckes et al suggest that virus and tumor cells share common strategies in shaping a permissive microenvironment by modulating the cargo of secreted exosomes (Fig.…”
mentioning
confidence: 99%
“…Despite current limitations, the work by Meckes et al (1) in PNAS represents a significant step into the deciphering of the mixed signals that are transmitted by exosomes produced in virus-infected tumor cells. Although the convergence of viral and exosomal pathways has been proposed previously, our knowledge on the function of virus-modified exosomes in vivo remains at the beginning stages.…”
mentioning
confidence: 99%